Language Learning Media Development Innovation: Maximizing the Use of Artificial Intelligence (AI) Technology - Nafri Yanti; Arono Arono; Fina Hiasa; Agus Trianto; Rio Kurniawan; Desti Fatin Fauziyyah (Journal of Innovative Technology and Sustainability Education, 2026)
Objetive: This research aims to develop viewing learning media that instill a sense of caring, responsibility, honesty, discipline, and independence in junior high school students, thereby forming a strong foundation for their future personality. This also supports the digitalization of learning and the independent curriculum program that the government has launched. Method: The research method used is qualitative, focusing on the development of learning media in the form of animated videos. The research design, as articulated by Creswell (2009), facilitates an in-depth exploration of the phenomenon of AI implementation in language learning media. Results: Leonardo AI is a platform that creates artificial intelligence characters combined with art, allowing users to easily and quickly create various characters according to their wishes. By using AI, researchers can integrate educational values including religiousness, integrity, responsibility, caring, discipline, humility, courage, patience, obedience, optimism, and hard work. Novelty: The research findings suggest that, in the future, teachers will be able to proactively explore various sources of information to increase their capacity to use AI to create learning media. Apart from that, schools are also expected to provide special training facilities for teachers to understand and operate AI to support the learning process.